FTAs AND POLITENESS STRATEGIES USED BY CARL FREDERICKSEN IN THE MOVIE ENTITLED UP - KURNIAWAN, RIYAN HENU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Human beings as the part of the society cannot live without having a communication with each other. As the part of society, people use language communication every single time they live. Politeness here gives very important contribution part in communication. Politeness shows people how to keep the manner in conversation to avoid the conflict that may happen between both interlocutors. The related study with politeness is FTA (Face Threatening Act). It is a study that learns about positive and negative faces for being threatened. The application of politeness strategy will redress the FTA towards the addressee. The writer conducts a study about FTA and politeness strategy performed by the main character Carl Fredericksen in the movie ent it led ‘UP’. There are two problems of the study proposed by the writer: (1) What Face Threatening Acts (FTAs) are performed by Carl in conversation occurring in the movie “UP”? (2) What types of politeness strategies are performed by Carl in conversat ion occurring in the movie “UP”?This study uses qualitative approach in relation to the use of clear andsystematic description about the phenomena being studied. Descriptive study intextual analysis is applied in this study to analyze conversation of the main character through the script of UP movie. The theory used by the writer is Brown and Levinson’s theory of politeness strategies.This study reveals that all of the faces, both positive and negative faces, arebeing threatened. The politeness strategies are also applied in the conversation, all the four types of politeness strategies, namely bald on-record politeness strategy, positive politeness strategy, negative politeness strategy, and off record, were embodied by Carl.The writer suggests students of Study Program of English conduct the deeperstudy about politeness strategies and FTA. He also hopes that the next researchers will relate the politeness strategy with other fields such as politeness maxim or something else. Keywords: politeness strategies, Face Threatening Act (FTA).